Skipping EXON-v6 from CD44V6-containing isoforms influences chemotherapy response and self-renewal capacity of gastric cancer cells - Lobo, S (2020)
De novo expressed CD44 isoforms containing exon-v6 are frequently associated with gastric cancer (GC) aggressiveness, and may predict chemotherapy response in vitro. Whether exon-v6 itself is responsible for conferring these properties to CD44v6-containing isoforms remains to be elucidated. CRISPR/Cas9 and Phosphorodiamidate Morpholino oligomers (PMOs) were used to induce specific exon-v6 skipping, maintaining the CD44 reading frame, in two GC cell lines endogenously expressing CD44v6. Cisplatin and 5-fluorouracil treatment response, and self-renewal ability was compared between CRISPR/Cas9-edited, CD44v6 knockdown and mock cells. We obtained homozygous genome-edited cell lines with exon-v6 deletion. Edited cells transcribed CD44v isoforms presenting in frame v5–v7 splicing, mimicking exon-v6 skipping. Results showed that removing specifically exon-v6 sensitizes cells to cisplatin and impairs cells’ self-renewal ability, similarly to CD44v6 knockdown. In parallel, we also tested a clinically feasible approach for transient exon-v6 skipping with a PMO-based strategy. We demonstrate that exon-v6 specific removal from CD44v isoforms increases cell sensitivity to cisplatin and impairs GC cells self-renewal. We trust that a PMO approach designed towards CD44v6 overexpressing GC cells may be a suitable approach to sensitize tumor cells for conventional therapy.